2023
DOI: 10.1371/journal.pone.0286126
|View full text |Cite
|
Sign up to set email alerts
|

Depressive rumination and trait anxiety mediate the effects of childhood victimization on adulthood depressive symptoms in adult volunteers

Abstract: Background Prior studies have reported that childhood victimization experiences substantially augment the risk of depression and suicide in adulthood. Several of our previous studies suggested that childhood experiences of victimization interact with the quality of parenting experienced in childhood, childhood experiences of abuse, neuroticism, and other factors to influence depressive symptoms in adulthood. In this study, it was hypothesized that “childhood victimization” worsens “trait anxiety” and “depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 48 publications
(85 reference statements)
2
5
0
Order By: Relevance
“…Our findings that rumination (reflection and brooding) mediated the relationship between childhood trauma and depression symptoms aligns with previous studies (Fang et al, 2023 ; Mansueto et al, 2021 ; Mao et al, 2023 ; Masuya et al, 2023 ). Childhood trauma is often challenging to openly talk about and tends to be repressed, so that it might resulting in the development of a ruminative pattern of thinking (Kim et al, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings that rumination (reflection and brooding) mediated the relationship between childhood trauma and depression symptoms aligns with previous studies (Fang et al, 2023 ; Mansueto et al, 2021 ; Mao et al, 2023 ; Masuya et al, 2023 ). Childhood trauma is often challenging to openly talk about and tends to be repressed, so that it might resulting in the development of a ruminative pattern of thinking (Kim et al, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…Rumination is likely to have a positive predictive effect on the evolution, severity, maintenance, and recurrence of depression and predicts the onset of depressive episodes (Stange et al, 2016 ). The relationship between rumination and childhood trauma and depression has been indicated in some studies (Deguchi et al, 2021 ; Masuya et al, 2023 ; Muñoz & Hanks, 2021 ). These studies have shown greater childhood trauma leads to higher levels of depression by increasing rumination.…”
mentioning
confidence: 94%
“…We recently reported on the effects of childhood peer victimization on trait anxiety. 30 In that study, as in the present report, a cross-sectional questionnaire survey in adult volunteers demonstrated that childhood experience of peer victimization augmented depressive symptoms by enhancing trait anxiety and further augmenting depressive rumination. In addition, childhood abuse shares similarities with childhood peer victimization in that it is an experience of being harmed by others in childhood.…”
Section: Discussionsupporting
confidence: 69%
“…The previous finding that childhood peer victimization experiences augment depressive rumination via trait anxiety strongly supports this idea. 30 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation